Disain Smart Electricity Penghematan pada Peralatan Listrik Menggunakan Sensor Ultrasonic - F I Pasaribu; A G Lubis; M Safril; B S Kusuma; M Fadlan (Cered Indonesia Institute, 2021)
Waste of electricity is a problem that often occurs accidentally, especially in household electricity, especially on electrical equipment that is routinely used but forgets to turn it off if there are no users around electrical equipment such as fans, air conditioners, TVs and others. Saving electrical energy is an action to reduce the amount of electrical energy use. This study aims to create a control device for saving electricity consumption. Saving electricity consumption does not mean not using electrical energy for something that is not useful, however, energy savings can be achieved by using energy efficiently where the same benefits are obtained by using less energy. This study uses a design method or is designed to be smart electricity using sensors. ultrasonic with arduino uno, where this tool controls daily use in case of forgetting so that no energy is wasted (waste of electricity) or more practical in controlling electrical equipment. Based on the results of tool testing and data analysis carried out, it was concluded that the working system of this tool succeeded in controlling the use of electronic equipment by detecting the presence of an object / human with the help of an ultrasonic sensor with a horizontal area range. The Radio Frequency Identification sensor is an additional sensor to help the Ultrasonic sensor improve to detect in a wider range of vertical areas by scanning the card. The total cost of the entire expenditure for 1 month is Rp. 203,365 using a smart electricity design tool as a means of saving and the use of electricity based on ultrasonic sensors using Arduino Uno and Rp. 418,175 without tools results in a difference in savings of Rp. 214.810,-